Assessment of Fish Species Composition and Abundance at Selected Landing Sites Along the Upper Benue River Basin in Taraba State, Nigeria - David, Delphine Leila; Godwin, Chinyere Ojiofor; Garkida, David Musa; Emmanuel, Allahnanan (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study assesses fish species composition and abundance at selected landing sites along the Upper Benue River Basin in Taraba State, Nigeria. Fish sampling was conducted monthly over six months (February to August 2022) at Mayo-Renewo and Lau landing sites using various fishing methods, including traps, gillnets, and hook and line. A total of 6,519 fish specimens from 26 species and 22 families were recorded. The dominant species were Tilapia galilaeus, Distichodus rostratus, and Alestes macroplepidotus in Mayo-Renewo, while Clarias gariepinus, Heterotis niloticus, and Alestes macroplepidotus were most abundant in Lau. The Shannon-Weiner Diversity Index indicated moderate species diversity, with values of -3.20703 at Mayo-Renewo and -3.28523 at Lau. Length-weight relationships showed positive allometric growth in most species, with a mean condition factor (K) above 1, indicating a favorable aquatic environment. Physicochemical analyses revealed variations in temperature (21.46–24.58°C), dissolved oxygen (6.1–8.4 mg/L), pH (8.22–8.62), electrical conductivity (340–840 µS/cm), total dissolved solids (170–556 mg/L), and turbidity (192–320 NTU). Statistical analysis (ANOVA) confirmed significant seasonal differences in these parameters (p < 0.05). The findings highlight the ecological health of the river and the importance of continuous monitoring to sustain fish biodiversity and productivity.